Synthesis and regulation of chlorogenic acid in potato: Rerouting phenylpropanoid flux in HQT‐silenced lines. Issue 4 (25th November 2014) - Payyavula, Raja S.; Shakya, Roshani; Sengoda, Venkatesan G.; Munyaneza, Joseph E.; Swamy, Prashant; Navarre, Duroy A.
Summary: Chlorogenic acid (CGA) is the major phenolic sink in potato tubers and can constitute over 90% of total phenylpropanoids. The regulation of CGA biosynthesis in potato and the role of the CGA biosynthetic gene hydroxycinnamoyl CoA:quinate hydroxycinnamoyl transferase ( HQT) was characterized. A sucrose induced accumulation of CGA correlated with the increased expression of phenylalanine ammonia‐lyase ( PAL) rather than HQT . Transient expression of the potato MYB transcription factor StAN1 (anthocyanin 1) in tobacco increased CGA. RNAi suppression of HQT resulted in over a 90% reduction in CGA and resulted in early flowering. The reduction in total phenolics and antioxidant capacity was less than the reduction in CGA, suggesting flux was rerouted into other phenylpropanoids. Network analysis showed distinct patterns in different organs, with anthocyanins and phenolic acids showing negative correlations in leaves and flowers and positive in tubers. Some flavonols increased in flowers, but not in leaves or tubers. Anthocyanins increased in flowers and showed a trend to increase in leaves, but not tubers. HQT suppression increased biosynthesis of caffeoyl polyamines, some of which are not previously reported in potato. Decreased PAL expression and enzyme activity was observed in HQT suppressed lines, suggesting the existence of a regulatory loop between CGA and PAL. Electrophysiology detected no effect of CGA suppression on potato psyllid feeding. Collectively, this research showed that CGA in potatoes is synthesized through HQT and HQT suppression altered phenotype and redirected phenylpropanoid flux.